New Insights In Intestinal Sar1B GTPase Regulation and Role in Cholesterol Homeostasis. Issue 10 (October 2015) - Sané, Alain; Seidman, Ernest; Spahis, Schohraya; Lamantia, Valérie; Garofalo, Carole; Montoudis, Alain; Marcil, Valérie; Levy, Emile
ABSTRACT Sar1B GTPase is a key component of Coat protein complex II (COPII)‐coated vesicles that bud from the endoplasmic reticulum to export newly synthesized proteins. The aims of this study were to determine whether Sar1B responds to lipid regulation and to evaluate its role in cholesterol (CHOL) homeostasis. The influence of lipids on Sar1B protein expression was analyzed in Caco‐2/15 cells by Western blot. Our results showed that the presence of CHOL (200 μM) and oleic acid (0.5 mM), bound to albumin, increases Sar1B protein expression. Similarly, supplementation of the medium with micelles composed of taurocholate with monooleylglycerol or oleic acid also stimulated Sar1B expression, but the addition of CHOL (200 μM) to micelle content did not modify its regulation. On the other hand, overexpression of Sar1B impacted on CHOL transport and metabolism in view of the reduced cellular CHOL content along with elevated secretion when incubated with oleic acid‐containing micelles for 24 h, thereby disclosing induced CHOL transport. This was accompanied with higher secretion of free‐ and esterified‐CHOL within chylomicrons, which was not the case when oleic acid was replaced with monooleylglycerol or when albumin‐bound CHOL was given alone. The aforementioned cellular CHOL depletion was accompanied with a low phosphorylated/non phosphorylated HMG‐CoA reductase ratio, indicating elevated enzymatic activity. Combination of Sar1B overexpression with micelle incubation led to reduction in intestinal CHOL transporters (NPC1L1, SR‐BI) and metabolic regulators (PCSK9 and LDLR). The present work showed that Sar1B is regulated in a time‐ and concentration‐dependent manner by dietary lipids, suggesting an adaptation to alimentary lipid flux. Our data also suggest that Sar1B overexpression contributes to regulation of CHOL transport and metabolism by facilitating rapid uptake and transport of CHOL. J. Cell. Biochem. 116: 2270–2282, 2015. © 2015 Wiley Periodicals, Inc.